Influence of Gender on the Supervisory Relationship: A Review of the Empirical Research from 1996 to 2010 - Hindes, Yvonne L.; Andrews, Jac J. W. (Canadian Journal of Counselling and Psychotherapy, 2011)
Twelve empirical studies published since 1996 regarding the effects of gender on the supervisory relationship are reviewed. Each study was reviewed and critiqued in relation to its methodology, research design, critical findings, and limitations. The results of these studies indicate that (a) gender influences the openness and affiliation one experiences in supervision, (b) care and concern are important to master-level supervisees, (c) female supervisors have a greater relationship focus than do male supervisors, (d) male supervisors rate hypothetical supervisees more negatively when the supervisee is depicted as female than when the supervisee is male, (e) females are more conservative than males on boundary negotiations, and (f) supervisors use different strategies with male and female supervisees. The majority of these studies have research design limitations that limit the generalization of findings. Results are discussed in relation to best practices and future directions for research.